Hubungan Self-Efficacy Terhadap Tingkat Kecemasan Mahasiswa Pendidikan Jasmani Tingkat Pertama - Mulya, Gumilar; Agustryani, Resty; Indrawan, Budi (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study aims to analyze the relationship between Self- efficacy and anxiety levels in first-year Physical Education students. Self-efficacy, which is an individual's belief in their ability to complete tasks or face challenges, is believed to play an important role in managing anxiety, especially in students who often face academic and social pressures. This study used a quantitative approach with a correlational design, involving 100 Physical Education students selected using a purposive sampling technique. Data were collected through the General Self-efficacy Scale (GSES) and State-Trait Anxiety Inventory (STAI) questionnaires. The results of the analysis showed that most students had moderate to high levels of Self-efficacy, and anxiety levels in the moderate category. The Pearson correlation test showed a significant negative relationship between Self-efficacy and anxiety (r = -0.65, p <0.05), which means that the higher the students' Self-efficacy, the lower the level of anxiety they experience. The results of the linear regression analysis showed that Self-efficacy can predict anxiety levels (R² = 0.42). These findings provide an important contribution to understanding the psychological dynamics of first-year college students, particularly in the context of Physical Education, and emphasize the importance of strengthening Self-efficacy to reduce academic anxiety.